A systematic review of structures, and geometries of the thermoelectric generators - Farheen F. Jaldurgam (17302762) (2022)
This systematic review presents the experimental and numerical optimization of the structure, design, and geometry of thermoelectric generators (TEGs). The critical aspect of this study is to evaluate the structures of different TEG designs in terms of their electric and thermal equivalent models. Thermal stress, contact resistance, heat pipe, and pulsed heating and cooling optimization have been judgmentally reviewed. This article will serve as a valuable and indispensable source of information on all aspects of thermoelectric design, structure, and geometry optimization. Other Information Published in: Applied Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/appl.202200074